Optimizing Employee Engagement Post Mergers and Acquisitions in Nepalese Commercial Banks: A Comprehensive Examination of Key Influencing Factors - Poudel, Omkar; Rijal, Umesh; Acharya, Pradeep (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Mergers and acquisitions in Nepal's banking industry are experiencing a surge due to regulatory pressures and various other factors. However, these deals pose several challenges, including employee disengagement. Despite the upward trend in mergers and acquisitions, the researches on the factors influencing the engagement level of the employees, particularly among Nepalese commercial banks, are lacking. Nepalese commercial banks significantly neglect the level of the engagement of employees. Thus, this study delves into how various factors, such as leadership and communication styles, career development opportunities, incentives and benefits, health and safety provision impact employee engagement in the aftermath of mergers and acquisitions transactions. The study employs quantitative research design, utilizing structured questionnaires for data collection. A total of 372 responses from employees across various commercial banks, spanning different corporate hierarchies, who have remained employed in banks that underwent mergers and acquisitions since 2020, have been gathered and utilized for subsequent analysis. The study's findings shed light on different factors affecting employee engagement and the level of their impact on employee engagement during mergers and acquisitions in Nepalese commercial banks. These findings provide practical insights for management bodies, human resource professionals, and policymakers, underscoring the importance of considering these factors when planning and executing mergers and acquisitions activities.